Perspectives of Meat Eaters on the Consumption of Cultured Beef (in vitro Production) From the Eastern Cape of South Africa - Falowo, Bamidele Andrew; Hosu, Yiseyon Sunday; Idamokoro, Emrobowansan Monday (Frontiers in Sustainable Food Systems, 2022)
The creation and growing popularity of cultured meat has raised mixed reactions among consumers about its originality, acceptability, edibility and nutritional quality across the world. The perception and reaction of consumers on the novel meat depend on diversity of factors including geographical location, media coverage, educational status, culture and religion. Therefore, this study was designed to examine the perceptions of consumers on consumption of natural versus cultured beef in Eastern Cape Province, South Africa. A total of 255 respondents were interviewed using structured questionnaires and the data were analyzed using descriptive statistics and X2 tests. The results revealed majority (63%) of the respondents have not heard about the concept of cultured beef production, of which 27 % of them were males and 36%, females. More than half (53%) of the respondents indicated their willingness to eat cultured beef if offered to them. Among all factors that were analysed, the participant level of education were found to significant influence their willingness to eat cultured beef when available commercially. It is therefore concluded that majority of consumers in this study supported the concept of cultured meat as an alternative way to compliment conventional meat production and would be willing to eat when provided.